FPGA Implementation of Canny Edge Detection Algorithm (International Journal of Engineering and Computer Science, 2014)
Edge detection is the first step in many computer vision applications. Edge detection of image significantly reduces the amount of data and filters out unwanted or insignificant information and gives the significant information in an image. This information is used in image processing to detect objects in which there are some problems like false edge detection, missing of low contrast boundaries, problems due to noise etc. In this paper Canny Edge Detection algorithm is implemented. Canny Edge Detection algorithm for stored image is implemented on Virtex 5 Field Programmable Gate Array (FPGA) board. Using Xilinx platform studio and Xilinx ISE output image displayed on Video Graphics Array (VGA) monitor which is interfaced with board by using DVI connector.